Penerapan Foot Massage terhadap Tingkat Nyeri Klien Post Operasi Sectio Caesarea di RSUD Kartini Karanganyar - Vita Fatika Sari; Maryatun Maryatun; Dewi Listyorini (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Post Sectio Caesarea mothers will feel pain in the incision wound or surgical area. Pain will hinder Activities of Daily Living (ADL), attachment bonding and mobilization due to an increase in pain intensity when the mother moves. One of the non-pharmacological pain management methods is massage. The massage that can be done on Post Sectio Caesarea mothers is foot massage, because the nocireceptors or nerves that initiate the sensation of pain are located on the surface of the internal tissue and under the dense skin of the feet. Objective: To determine the results of the implementation of foot massage on the pain level of clients after caesarea section surgery at Kartini Karanganyar Regional Hospital. This research is a case study with a pre-experimental method with one group pre test-post test design. Using 2 respondents, pre-test and post-test pain scale measurements were carried out. Foot massage was carried out once with a duration of 20 minutes for 2 days, the pain scale was measured using the Numeric Rating Scale (NRS). The client's pain scale after caesarea section surgery before being given foot massage was in the moderate scale category and after being given foot massage it became light scale pain. There is a decrease in the client's pain scale after caesarea section surgery before and after being given foot massage in the Teratai 1 Room at Kartini Karanganyar District Hospital.